Voice over 802.11 - Ohrtman, Frank (Artech House, 2011)
Wi-Fi can further enhance your organization's productivity and savings by increasing portability and eliminating charges for PBX maintenance and for wire-line and cellular phone service. However, concerns about the QoS of Wi-Fi and VoIP prevent many organizations from realizing the full savings and productivity improvements that Wi-Fi can deliver. This guide to deploying Wi-Fi telephony helps you overcome these concerns by showing in detail how to engineer each component of Wi-Fi for reliable, high- quality voice transmission. This informative reference reveals how Voice over Wi-Fi is a scalable, secure networking solution that supports today's demanding application needs. The book explains the ins and outs of the 802.11 standard, Softswitch architecture and applications, and related transport network technology so you can deploy full-featured Wi-Fi that has optimum range and signalling. You also learn the economics of 802.11 and Softswitch so you can measure the cost savings and return on investment of deploying Wi-Fi.